Clarification of creep deformation mechanism in heat-affected zone of 9Cr steels with In Situ experiments. (15th March 2021) - Wang, Yiyu; Zhang, Wei; Huang, Hui; Wang, Yanli; Zhong, Weicheng; Chen, Jian; Feng, Zhili
Abstract: This work quantified nonuniform creep deformation across the heterogeneous heat-affected zone (HAZ) of Grade 91 steel with sophisticated experiments, including an electric-thermal finite element model–assisted Gleeble thermomechanical simulation and a high-temperature creep testing with in situ digital image correlation (DIC). High temperature creep properties of HAZ sub-zones were quantitatively measured by the DIC. By utilizing peak temperature, hardness, local creep strain, and underlying microstructures, creep deformation mechanisms in HAZ were further understood. DIC measurements reveal a creep-vulnerable zone (CVZ) exposed to a peak temperature of 932°C (close to AC 3 ) in the intercritical HAZ experienced the fastest creep strength degradation instead of the soft zone with the lowest hardness prior to creep. The significantly reduced precipitation strengthening from misplacement of undissolved and coarsened M 23 C 6 carbides led to a faster recrystallization of tempered martensite in the CVZ. Weak untransformed tempered martensite (ferrite grains) stabilized by local Cr enrichment from dissolved M 23 C 6 also harmed the CVZ's creep resistance. Graphical abstract: Image, graphical abstract